A Polarization Boosted Strategy for the Modification of Transition Metal Dichalcogenides as Electrocatalysts for Water‐Splitting. Issue 26 (3rd June 2021) - Chen, Guanyu; Zhang, Chang; Xue, Shuyan; Liu, Jiwei; Wang, Yizhe; Zhao, Yunhao; Pei, Ke; Yu, Xuefeng; Che, Renchao
Abstract: The design and fabrication of transition metal dichalcogenides (TMDs) are of paramount significance for water‐splitting process. However, the limited active sites and restricted conductivity prevent their further application. Herein, a polarization boosted strategy is put forward for the modification of TMDs to promote the absorption of the intermediates, leading to the improved catalytic performance. By the forced assembly of TMDs (WS2 as the example) and carbon nanotubes (CNTs) via spray‐drying method, such frameworks can remarkably achieve low overpotentials and superior durability in alkaline media, which is superior to most of the TMDs‐based catalysts. The two‐electrode cell for water‐splitting also exhibits perfect activity and stability. The enhanced catalytic performance of WS2 /CNTs composite is mainly owing to the strong polarized coupling between CNTs and WS2 nanosheets, which significantly promotes the charge redistribution on the interface of CNTs and WS2 . Density functional theory (DFT) calculations show that the CNTs enrich the electron content of WS2, which favors electron transportation and accelerates the catalysis. Moreover, the size of WS2 is restricted caused by the confinement of CNTs, leading to the increased numbers of active sites, further improving the catalysis. This work opens a feasible route to achieve the optimized assembling of TMDs and CNTs for efficient water‐splitting process. Abstract : A universal polarization boosted strategy is put forward for the modification of transition metal dichalcogenides (TMDs) to form a composite of carbon nanotubes and TMDs. The composite exhibits outstanding HER/OER performance and can be used as the catalyst of water‐splitting. This work may serve as a strong foundation for improving the TMDs‐based catalysts and provide insights for future predictive synthesis.